3D and 2D growth of SnO2 nanostructures on Ga2O3 nanowires: synthesis and structural characterization. Issue 41 (2nd October 2017) - Alonso-Orts, M.; Sánchez, A. M.; López, I.; Nogales, E.; Piqueras, J.; Méndez, B.
Abstract : In this work, a simple thermal evaporation method has been used to obtain a variety of Ga2 O3 /SnO2 nano-assemblies with different shapes and dimensionalities, which may affect their physical properties, especially those influenced by surface properties. Abstract : In this work, a simple thermal evaporation method has been used to obtain a variety of Ga2 O3 /SnO2 nano-assemblies with different shapes and dimensionalities, which may affect their physical properties, especially those influenced by surface properties. The obtained nanostructures have been characterized using electron microscopy-related techniques in order to understand their growth mechanisms. By using both metallic gallium and tin oxide powders as precursors, Ga2 O3 nanowires (straight or branched) decorated with SnO2 nanoparticles or SnO2 quasi-two dimensional plates have been produced after dynamic thermal annealing for 2.5, 8.0 and 15.0 hours. For shorter treatments, accumulation of Sn atoms at the Ga2 O3 nanowire surface or defect planes has been observed by high resolution TEM, which suggests that they could act as nucleation sites for the further growth of SnO2 . On the other hand, longer treatments promote the formation of Ga-doped SnO2 belts, from which SnO2 nanowires eventually emerge. High-resolution TEM imaging and microanalysis reveal that Ga accumulation at (200) SnO2 planes could stabilize some non-stoichiometric or intermediate tin oxide phases, such as Sn2 O3, at local areas in the belts. The presence of non-stoichiometric tin oxide is relevant in applications, since surface states affect the physical–chemical behavior of tin oxide.